Maneke as Local Wisdom in the Community of Small Islands in Sangihe Island Regency, North Sulawesi - Jane Sulinda Tambas; Kliwon Hidayat; Abdul Latief Abadi; Charles Kepel (Program Pascasarjana, 2017)
Maneke is one of the local wisdom in Sangihe Islands Regency, inherited from the ancestors of the people of Sangihe. Maneke contains the norms and values of life and customs to keep the mutual relationship between humans and nature. This local wisdom, however, has gradually become extinct. The aim of the research was to describe the Maneke as a local wisdom in Sangihe Islands. Sangihe Island Regency is one of a cluster of islands located in North Sulawesi province with 150 islands, 26 inhabited and 79 uninhabited islands. There are two islands on the cluster of uninhabited islands located in two Districts in Sangihe. The focus of this research is done on the Batunderang Island in the Sub-district of South Manganitu and Para Island in the District of Tatoareng. This study used a qualitative approach to the design ethnography emphasizes the natural setting to see, learn, express and understand how to observe, and observations with in-depth interviews and conduct focus group discussions with community members, traditional leaders, public figures, figures from religious leaders and members of the implementation group of Maneke. Maneke is a socio-cultural system that has a socio-cultural elements contained in the components of the superstructure ideology, social structure and infrastructure material. Maneke is the component of the superstructure ideology because it has cultural values and norms into view, knowledge, activity and behavior patterns which are actualized in the traditions, customs, rituals beliefs or religion.Keywords: local knowledge, Maneke, marine tourism, Sangihe Island.